2020
DOI: 10.2298/ciceq190708034v
|View full text |Cite
|
Sign up to set email alerts
|

Kombucha fermentation of six medicinal herbs: Chemical profile and biological activity

Abstract: Article Highlights • Kombucha on medicinal plants was characterized • Higher antioxidant activity of herbal kombucha compared to traditional kombucha was established • Higher phenolic and flavonoids contents in herbal kombucha were determined • Elderberry kombucha beverage had the highest ACE inhibitory activity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…There was also a moderate correlation between the total phenolic and flavonoid substance of the samples (r=0.58, p<0.05). In their study, Vitas et al (8) prepared alternative kombucha drinks from six medicinal plants, namely winter savoury, peppermint, nettle, wild thyme, elderberry, and quince. They showed that alternative kombucha drinks prepared with winter savoury, peppermint and nettle had higher total flavonoid content than conventional products.…”
Section: Total Phenolic (Tpc) and Total Flavonoid (Tfc) Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…There was also a moderate correlation between the total phenolic and flavonoid substance of the samples (r=0.58, p<0.05). In their study, Vitas et al (8) prepared alternative kombucha drinks from six medicinal plants, namely winter savoury, peppermint, nettle, wild thyme, elderberry, and quince. They showed that alternative kombucha drinks prepared with winter savoury, peppermint and nettle had higher total flavonoid content than conventional products.…”
Section: Total Phenolic (Tpc) and Total Flavonoid (Tfc) Contentmentioning
confidence: 99%
“…3 investigated the use of different herbs in kombucha preparation and evaluated their antioxidant and antimicrobial activities (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…By day 15 of storage, a significant increase (p <0.05) was observed in the TA values, which fluctuated between 0.42%-1.61% (COr) and 0.44%-1.46% (CFr); the lowest values corresponded to the media containing saccharose as a carbon source (Table 1). According to previous studies [27,28,38,45], an increase in the TA values during the fermentation process can be associated with the metabolism of sugars into organic acids due to the effect of some yeasts and bacteria. The low TA values found in the saccharose-based medium can be attributed to the time of fermentation; since for this disaccharide, it is necessary first that the yeast converts the saccharose into glucose, and fructose through glycolysis, so that acetobacter can subsequently ferment these sugars for the acetic acid production.…”
Section: Ph Tss and Tamentioning
confidence: 91%
“…In this process, four different carbon sources were evaluated: Glucose, dextrose, fructose, and saccharose. The methodology was carried out as described in previous studies [25,28,38], but with some modifications related to water temperature, amount of sugar, and fermentation time. First, two liters of water were heated to a temperature of 85 • C. Once this temperature was reached, 3.6 g of green tea was added to each solution liter.…”
Section: Preparation Of Kombucha Cultures and Fermentationmentioning
confidence: 99%
See 1 more Smart Citation